THU0475 The Relation Between Disease Activity and Findings and Mean Platelet Volume in Behçet's Disease. (23rd January 2014) - Uzerk Kibar, M.; Kucuksahin, O.; Turgay, M.; Kınıklı, G.; Ates, A.
Abstract : Background: Behcet's Disease (BD), is a chronic multisystemic vasculitis that often presents with flares and is characterized by recurrent oral aphtous ulcers, genital ulcers, cutaneous lesions, ocular, gastrointestinal, articular, pulmonary, vascular and neurological involvement. In Behcet's disease, during recurrent inflammatory attacks, various vasculitic involvements may be seen in different systems. It is difficult to measure disease activity in these patients, because disease presents with attacks and relapses and there is no specific laboratory test that encompasses all findings of disease. In addition, there is no standard form evaluating the severity of disease activity. Objectives: The aim of the present study was to investigate the relation between clinical activity of Behcet's disease and mean platelet volume (MPV) Methods: 200 patients meeting 1990 classification criteria of International Behcet's disease Study Group and who were followed between October 2011 and june 2012 in Multidisciplinary Behcet's Disease outpatient clinic were included in the study. Files of BD patients in the archive of Behcet's disease outpatient clinic and data recorded in Electronic Health Records were examined. Symptoms present at the time of referral to outpatient clinic, examination findings, drug use, systematic involvement, and routine laboratory investigations were evaluated. Results: Patients were divided into two groups, patients with or without active disease were named group 1 and group 2, respectively. There were 100 patients in each group. Statistically significant difference was found between groups in terms of the age. (p<0.008). Active patients were established to be younger ones. With logistic regression analysis, it was established that erythema nodosum, papulopustular lesions, erythrocyte sedimentation rate, CRP, MPV and oral apthous lesions were independent factors predicting disease activity. In all BD patients with independent of disease activity, no significant difference was found between the patients with a history of thrombosis and those without it with respect to MPV (9.12 vs 8.89 fl, respectively, p=0, 117). In patients with active disease, MPV values were significantly higher than those of without active disease (9.43 vs 8.41 fl, respectively, p<0.05). In patients without active disease (group 2), there was borderline difference between the MPV values of those with a history of thrombosis and those without it (8.9 vs 8.35 fl, respectively, p<0, 05). Among patients with active disease (group 1), no significant difference in MPV values of those with a history of thrombosis and those without it was found ( 9.47 vs 9.27 fl, p>0.05). No relation was found between other system involvement of Behcet's disease and MPV. Conclusions: The higher MPV values in BD patients seem to be independent factor predicting disease activity. Further prospective studies with larger patient series addressing the factors that playing a role in the regulation of MPV will help to determine disease activity early, aiding the physicians to take the necessary measures and guide treatment. References: Yazıcı H, Yurdakul S, Hamuryudan V. Behcet's syndrome. Curr Opin Rheumatol 1999; 11: 53-57 Lee WS, Kim TY. Is mean platelet volume increased in behcet's disease with thrombosis?Tohoku J Exp Med. 2010 ;222(3):225-6 Disclosure of Interest: None Declared